UJI EFEKTIVITAS MIKROBA ANTAGONIS TERHADAP PATOGEN PENYEBAB BUSUK BUAH KAKAO - SUDARMA, I MADE; SUSANTA WIRYA, I G. N. A. (AGRITROP; Vol. 28, No. 3 September 2009, 2012)
Pod rot disease in cacao (Theobroma cacao) caused by Phytophthora palmivora has been loss until 90%. The major economic loss is from infection of the pod. Pods can be infected at any age, but most significant economic loss arises from infection during the two months prior to ripening. Pod infected at this stage can be a total loss because the fungus can easily pass from the pod husk to the seed-coat of the bean in a cacao still be convergent only at usage of synthetic pesticide. Therefore need to be searched other alternative to control the disease, namely by exploiting antagonist microbe. Research has been done in Laboratory of Microbiology and Microbial Pesticide, Department of Agroecotechnology, Faculty of Agriculture, Udayana University, Jl. PB. Sudirman Denpasar, from April until October 2007. There are three research phases done like : 1) insulation pathogen cause of disease, 2) antagonist microbe inhibitory activity test to growth of pathogen in vitro, and 3) inhibitory activity test free cell antagonist microbe to growth of pathogen in vitro. Result of research shows, found two species pathogen cause of pod rot disease of cacao namely Phytophthora sp. (A) and Phytophthora sp. (B). Based on result of examination out of four antagonist microbes tested like Trichoderma sp.; Saccharomyces sp.; Pseudomonas fluorescens and Bacillus sp., that is most effective in depressing pathogen is Trichoderma sp. with inhibitory activity equal to 83,98% to Phytophthora sp. (A) and 82,18% to Phytophthora sp. (B) at PDA media. Secondary metabolite released by fourth of antagonist microbe depress both pathogen cause of pod rot disease of cacao at PDA media.
Keywords: Pod rot disease, cacao (Theobroma cacao), and antagonist microbes